Targeting Virulence in Staphylococcus aureus by Chemical Inhibition of the Accessory Gene Regulator System In Vivo - Salam, Akram M. (mSphere, 2018)
Methicillin-resistant Staphylococcus aureus (MRSA) presents one of the most serious health concerns worldwide. The WHO labeled it as a “high-priority” pathogen in 2017, also citing the more recently emerged vancomycin-intermediate and -resistant strains. With the spread of antibiotic resistance due in large part to the selective pressure exerted by conventional antibiotics, the use of antivirulence strategies has been recurrently proposed as a promising therapeutic approach. In MRSA, virulence is chiefly controlled by quorum sensing (QS); inhibitors of QS are called quorum quenchers (QQ). In S. aureus, the majority of QS components are coded for by the accessory gene regulator (Agr) system. Although much work has been done to develop QQs against MRSA, only a few studies have progressed to in vivo models. Those studies include both prophylactic and curative models of infection as well as combination treatments with antibiotic. For most, high efficacy is seen at attenuating MRSA virulence and pathogenicity, with some studies showing effects such as synergy with antibiotics and antibiotic resensitization. This minireview aims to summarize and derive conclusions from the literature on the in vivo efficacy of QQ agents in MRSA infection models. In vitro data are also summarized to provide sufficient background on the hits discussed. On the whole, the reported in vivo effects of the reviewed QQs against MRSA represent positive progress at this early stage in drug development. Follow-up studies that thoroughly examine in vitro and in vivo activity are needed to propel the field forward and set the stage for lead optimization.